Evaluación de tres inductores de floración en el cultivo de mango (Mangifera indica), comunidad de Pueblo nuevo, cantón Bolívar, Carchi. - Vasquez Chamorro, Christian Geovanny (2024)
The present research was carried out in the community of Pueblo Cantón Bolívar in the mango orchard of Mr. Hernan Villlarreal with the purpose of evaluating three types of phytohormones gibberellin, auxin and cytokinin with a dose of 30 ml / l, with foliar application of 4 liters per five-year-old mango tree of the Tommy Atkins variety, data collection was carried out once the buds of the mango branches presented the characteristics of optimal maturity for the application of phytohormones, to meet the proposed objectives. In the research, the experimental design of completely randomized block design (DBCA) was applied, each experimental unit constituted a five-year-old mango tree with a height of 2.50 m, the treatments applied were three plant phytohormones\; gibberellin (T1), auxin (T2), cytokinin (T3) and a control (T4) without phytohormones. The study slope variables were days to flowering, number of flowers per plant (panicle), number of fertilized flowers, number of fertilized flowers, number of aborted flowers and percentage of fertilization. The data obtained were subjected to normality tests. Shapiro Wilk and Homostecity with Levene's test, with the values of (p-value >0.05) of the variables\; according to the data obtained. Finally, with respect to the results, it was observed when applying the analysis of variance for the treatments that they are highly significant, accepting the alternative hypothesis that at least one phytohormone affects floral induction in the mango crop (Mangifera indica), according to the conditions. agroclimatic conditions in the study area, Pueblo Nuevo, Bolívar, Carchi. It was concluded that gibberellin phytohormone at a dose of 30 m/l is the best treatment for flowering induction with three applications every 15 days.